The concept of preparation of RC-pilotless microplanes - Матійчик, М.П. (Proceedings of National Aviation University (archive), 2005)
It is specified on necessity of realization of special preparation of pilots for RC-pilotless microplanes. It is considered a line of analogies and original causes which result in necessity of raining and it is offered a technique of the last.